Impulsive Consensus Tracking of Multiagent Systems with Quantization and Input Delays Using Position-Only Information. (20th February 2014) - Zhou, Hong; Qin, Yu-Zhen; Feng, Kuo; Hu, Wen-Shan; Liu, Zhi-Wei
Abstract : This paper investigates the consensus tracking problem for second-order multi-agent systems without/with input delays. Randomized quantization scheme is considered in the communication channels, and impulsive consensus tracking algorithms using position-only information are proposed for the consensus tracking of multi-agent systems. Based on the algebraic graph theory and stability theory of impulsive systems, sufficient and necessary conditions for consensus tracking are studied. It is found that consensus tracking for second-order multi-agent systems without/with input delays can be achieved by appropriately choosing the sampling period and control gains which are determined by second/third degree polynomials. Simulations are performed to validate the theoretical results.